Isopropyl alcohol gas sensitive material and preparation method and application thereof
By using nanorod-shaped α-Fe2O3 and nanoparticle-shaped BiFeO3 composite materials in isopropanol gas sensors and doping them with rGO, the problem of low sensor sensitivity and response performance is solved, and more efficient and stable gas detection is achieved, reducing energy Consumption and operating temperature.
Patent Information
- Application Number
- CN202411245214.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The sensitivity and response performance of existing isopropanol gas sensors are low, especially sensors based on α-Fe2O3 materials, which limit their application; the gas-sensitive characteristics of BiFeO3 in sensors are limited, and the electron-hole recombination speed is fast, The specific surface area is small, which affects the gas adsorption efficiency.
The p-n heterostructure was prepared by composited nanorod-shaped α-Fe2O3 with nanoparticle-shaped BiFeO3 and doped with thin-film-shaped rGO to improve the specific surface area and conductivity of the material, thereby enhancing the response performance to isopropanol gas.
It significantly improves the sensitivity and response performance of isopropyl alcohol gas sensors, shortens the response/recovery time, improves the selectivity of materials and anti-interference ability, and reduces the operating temperature, achieving more energy-saving and green gas detection.
Smart Images

Figure CN118754205B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas-sensitive materials, and in particular relates to an isopropyl alcohol gas-sensitive material and a preparation method and application thereof. Background Art
[0002] Isopropyl alcohol is a colorless organic compound with a strong odor. The vapor density of isopropyl alcohol is greater than that of air. When exposed to air or other oxidants, it is highly flammable and has a relatively large combustion range. It can explode through deflagration. Isopropyl alcohol can cause certain harm to the human body. Long-term exposure to isopropyl alcohol gas will cause the skin to deflate. Lower concentrations of isopropyl alcohol will also irritate the human respiratory system and cause eye discomfort. In a high concentration environment, it will inhibit the human central nervous system and cause symptoms such as severe vomiting, respiratory failure and internal bleeding. Therefore, the development of high-performance isopropyl alcohol gas sensors can effectively protect the safety of people and property, which is a work of great practical significance.
[0003] Among the many types of gas sensors, metal oxide sensors have been widely studied and applied due to their simple manufacture, low price, portability and high sensitivity, and thus have become the preferred method for monitoring isopropyl alcohol gas in the present invention.
[0004] BiFeO3 has excellent gas-sensing properties. Compared with metal oxides such as ZnO, CuO and SnO2, its performance is more stable and reliable. BiFeO3 has unique surface properties and oxygen adsorption, which is of great help to improve gas selectivity. However, due to the fast recombination rate of BiFeO3 electron-hole pairs and its small specific surface area, the gas adsorption is limited, which affects the gas response performance. There is limited research on the gas-sensing properties of BiFeO3, so BiFeO3 has great research significance in the application of sensors. α-Fe2O3 has the advantages of low cost and easy preparation, but most gas sensors based on α-Fe2O3 have low sensitivity, which greatly limits the application of α-Fe2O3-based gas sensors; although the composite preparation of pn heterostructures by α-Fe2O3 and BiFeO3 can improve the response ability of the material to a certain extent, it is limited by the conductivity and specific surface area of the material, which still has the problem of poor gas response in the field of gas-sensitive materials. Summary of the invention
[0005] The purpose of the present invention is to provide an isopropyl alcohol gas sensitive material, which can improve the gas sensing performance of α-Fe2O3, increase the reactive sites on the surface of the gas sensitive material, accelerate the adsorption and desorption of gas molecules, thereby improving the sensitivity of the sensor and shortening the response / recovery time.
[0006] In order to solve the above problems, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an isopropyl alcohol gas sensitive material, comprising nanorod-shaped α-Fe2O3, nanoparticle-shaped BiFeO3 and thin film rGO, wherein the nanoparticle-shaped BiFeO3 is uniformly attached to the nanorod-shaped α-Fe2O3, the thin film rGO is doped between the nanorod-shaped α-Fe2O3 to which the nanoparticle-shaped BiFeO3 is attached, the content of the thin film rGO is 0.50 to 1.50 wt % of the isopropyl alcohol gas sensitive material, and the molar ratio of the nanorod-shaped α-Fe2O3 to the nanoparticle-shaped BiFeO3 is 4 to 8:1.
[0008] Preferably, the content of the rGO is 1.0wt% of the isopropanol gas sensitive material, and the molar ratio of α-Fe2O3 to BiFeO3 is 6:1.
[0009] Preferably, the diameter of the nanorod-like α-Fe2O3 is 30 to 40 nm, and the length is 400 to 600 nm, the diameter of the nanoparticle-like BiFeO3 is 600 nm to 800 nm, and the size range of the thin film-like rGO is 50 to 600 nm.
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned isopropyl alcohol gas sensitive material, comprising the following steps:
[0011] S1. FeSO4·7H2O and CH3COONa·4H2O were added to deionized water, and after being completely dissolved, a water bath reaction was performed, followed by centrifugation and drying to obtain a yellow powder precursor α-FeOOH, which was then calcined to obtain nanorod-shaped α-Fe2O3;
[0012] S2. Dissolve Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, citric acid and nanorod-shaped α-Fe2O3 in a mixture of glycerol and anhydrous ethanol, and then perform a hydrothermal reaction, followed by washing, drying and calcining to obtain α-Fe2O3 / BiFeO3;
[0013] S3. Add graphene oxide to deionized water and disperse it evenly, then add concentrated ammonia water, hydrazine hydrate and α-Fe2O3 / BiFeO3; stir in a water bath to generate a precipitate, then centrifuge and dry the precipitate to obtain rGO-α-Fe2O3 / BiFeO3 gas sensitive material, i.e., isopropanol gas sensitive material.
[0014] Preferably, in step S1, the molar ratio of FeSO4·7H2O to CH3COONa·4H2O is 1:1.5-2, the water bath reaction temperature is 50-70°C, the reaction time is 1.0-1.5 hours; the calcination temperature is 450-550°C, and the calcination time is 2.5-3.5 hours.
[0015] Preferably, in step S2, the molar ratio of Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, citric acid and α-Fe2O3 is 1:1:1.1~1.15:4~8, the volume ratio of glycerol to anhydrous ethanol is 1:2~4, the hydrothermal temperature is 150~180°C, the reaction time is 10~14 hours; the calcination temperature is 400~600°C, and the calcination time is 3~5 hours.
[0016] Preferably, in step S3, the volume ratio of hydrazine hydrate to concentrated aqueous ammonia is 1:5-7, the water bath temperature is 70-90° C., and the water bath reaction time is 20-40 minutes.
[0017] In a third aspect, the present invention further provides an application of the above-mentioned isopropyl alcohol gas sensitive material in an isopropyl alcohol sensor.
[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0019] (1) The isopropanol gas sensitive material disclosed in the present invention, by doping with thin film rGO, not only increases the specific surface area of the material, providing more active sites for isopropanol gas analysis adsorption-desorption, but also the rGO film has good intrinsic electron mobility, improves the conductivity of the material, and thus improves the response performance of the material to isopropanol gas. The results of Experimental Example 3 show that the response value (7.34-8.93) of the three components doped with rGO to isopropanol gas is much higher than the response value (4.70-6.24) of α-Fe2O3 / BiFeO3 of different ratios to isopropanol gas, indicating that doping with rGO can improve the response performance to isopropanol gas.
[0020] (2) The isopropanol gas sensitive material disclosed in the present invention utilizes the unique surface properties and oxygen adsorption performance of BiFeO3 and the pn heterostructure prepared by compounding with α-Fe2O3 to regulate electrons and holes, thereby improving the selectivity and anti-interference ability of isopropanol gas. Experimental Example 4 tested a variety of different gases under the same conditions. The results showed that the response of rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material to isopropanol gas was much greater than that of other gases, indicating that the material has good selectivity.
[0021] (3) The chemical properties of α-Fe2O3 and BiFeO3 in the isopropanol gas sensitive material disclosed in the present invention are stable, so that the response of rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 to isopropanol gas has excellent stability. The test results of Experimental Example 5 show that the rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material has a small fluctuation in the test results of repeated testing of 25ppm isopropanol gas at 137°C for 6 times within 32 days, indicating that the gas sensor based on the gas sensitive material has good stability.
[0022] (4) The isopropanol gas sensitive material disclosed in the present invention forms a pn heterojunction by using nanorod-like α-Fe2O3 and nanoparticle-like BiFeO3, and is doped with rGO to improve the material's electrical conductivity and electron mobility. Experimental Example 6 tested the gas-sensitive response of rGO-α-Fe2O3 / BiFeO3 to 25ppm isopropanol gas at different temperatures. The results showed that the optimal operating temperature was 137°C. Compared with the prior art, the operating temperature is significantly lower, the energy consumption is reduced, and it is more energy-saving, green and environmentally friendly.
[0023] (5) The isopropanol gas sensitive material disclosed in the present invention forms a pn heterojunction through nanorod-shaped α-Fe2O3 and nanoparticle-shaped BiFeO3, and is doped with rGO, which improves the material's conductivity and electron mobility. The heterojunction can accelerate the transfer of electrons between different particles, shorten the time of gas-sensitive response, and thus has a fast response-recovery capability to isopropanol gas. Experimental Example 7 tested the response-recovery time of rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material to 25ppm isopropanol gas at 137°C. The response time was 16s and the recovery time was 29s, indicating that the gas sensor based on the gas sensitive material has a fast response-recovery capability.
[0024] (6) The isopropyl alcohol gas sensitive material disclosed in the present invention is prepared by a water bath method, a hydrothermal method and a hydrazine hydrate reduction method, and has the characteristics of being simple, easy to operate, low cost and readily available raw materials, thus providing an effective sensitive material for the development of high-performance isopropyl alcohol sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the SEM image of the synthetic sample of Example 2;
[0026] Figure 2 The SEM images of the α-Fe2O3 synthesized in Comparative Example 1 and the sample synthesized in Comparative Example 3;
[0027] Figure 3 XRD spectra of the samples synthesized in Examples 1-3 and Comparative Examples 1-4;
[0028] Figure 4 The selectivity performance diagram of the isopropyl alcohol sensor prepared in Example 2 and Comparative Examples 1 and 3;
[0029] Figure 5 This is a stable performance diagram of the isopropyl alcohol sensor prepared in Example 2;
[0030] Figure 6 Graph showing the operating temperatures of the isopropyl alcohol sensors prepared in Example 2 and Comparative Examples 1 and 3;
[0031] Figure 7 This is a response-recovery time diagram of the isopropyl alcohol sensor prepared in Example 2. DETAILED DESCRIPTION
[0032] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0033] The numerical values in the synthetic samples in the embodiments and comparative examples all represent the content of the substances. For example, 1.0wt% in the rGO-α-Fe2O3 / BiFeO3 gas sensitive material means that the rGO content is 1.0wt% of the isopropanol gas sensitive material, 6α-Fe2O3 / BiFeO3 means that the molar ratio of α-Fe2O3 to BiFeO3 is 6:1, and so on. Example 1
[0034] (1) Add 5.0 mmol of FeSO4·7H2O and 7.5 mmol of CH3COONa·4H2O to 50.00 mL of deionized water, stir and react in a 50°C water bath for 1.2 hours, then centrifuge and dry to obtain yellow powder α-FeOOH, which is calcined at 450°C for 3.5 hours to obtain α-Fe2O3;
[0035] (2) 1.6 mmol Bi(NO3)3·5H2O, 1.6 mmol Fe(NO3)3·9H2O, 1.76 mmol citric acid and 9.6 mmol α-Fe2O3 were added to a mixture of 10.00 mL glycerol and 20.00 mL anhydrous ethanol, and the mixture was hydrothermally reacted at 150°C for 14 hours. After the reaction, the mixture was cooled to room temperature, washed, dried and finally calcined at 450°C for 5 hours to obtain 6α-Fe2O3 / BiFeO3.
[0036] (3) Put 10 mg of GO into 150 mL of distilled water and disperse it evenly. Then add 2.5 mL of concentrated ammonia water, 0.50 mL of hydrazine hydrate and 2.0 g of 6α-Fe2O3 / BiFeO3 to the solution. Stir at 90 °C for 30 min, then centrifuge and dry the reaction solution to obtain rGO (0.5 wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material. Example 2
[0037] Compared with Example 1, the difference is that in step (1), 8.8 mmol of CH3COONa·4H2O is added, the water bath temperature is 70°C, the water bath time is 1 hour, the calcination temperature is 500°C, and the calcination time is 3 hours; in step (2), 1.8 mmol of citric acid, 10.00 mL of glycerol and 30.00 mL of anhydrous ethanol are added, the hydrothermal temperature is 160°C, the hydrothermal time is 12 hours, the calcination temperature is 500°C, and the calcination time is 4 hours; in step (3), 3.0 mL of concentrated ammonia water, 0.50 mL of hydrazine hydrate, and 1.0 g of 6α-Fe2O3 / BiFeO3 are added; the stirring water bath temperature is 70°C, and the water bath time is 20 minutes; the other parameters and steps are exactly the same as in Example 1, and rGO (1.0 wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material is obtained. Example 3
[0038] Compared with Example 1, the difference is that in step (1), 10 mmol of CH3COONa·4H2O is added, the water bath temperature is 60°C, the water bath time is 1.5 hours, the calcination temperature is 480°C, and the calcination time is 2.5 hours; in step (2), 1.84 mmol of citric acid, 10.00 mL of glycerol and 40.00 mL of anhydrous ethanol are added, the hydrothermal temperature is 180°C, the hydrothermal time is 10 hours, the calcination temperature is 550°C, and the calcination time is 3 hours; in step (3), 3.5 mL of concentrated ammonia water, 0.50 mL of hydrazine hydrate, 0.67 g of 6α-Fe2O3 / BiFeO3 are added, the stirring water bath temperature is 80°C, and the water bath time is 40 minutes; the other parameters and steps are exactly the same as in Example 1, and rGO (1.5wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material is obtained. Example 4
[0039] Compared with Example 1, the difference is that in step (1), 7.5 mmol of CH3COONa·4H2O is added, the water bath temperature is 50°C, the water bath time is 1 hour, the calcination temperature is 500°C, and the calcination time is 3 hours; in step (2), 6.4 mmol of α-Fe2O3, 1.76 mmol of citric acid, 10.00 mL of glycerol and 30.00 mL of anhydrous ethanol are added, the hydrothermal temperature is 170°C, the hydrothermal time is 13 hours, the calcination temperature is 400°C, and the calcination time is 3.5 hours; in step (3), 2.0 g of 4α-Fe2O3 / BiFeO3 is added; the other parameters and steps are exactly the same as in Example 1, and rGO (0.5wt%)-4α-Fe2O3 / BiFeO3 gas sensitive material is obtained. Example 5
[0040] Compared with Example 1, the difference is that in step (1), 9.0 mmol of CH3COONa·4H2O is added, the water bath temperature is 65°C, the water bath time is 1.4 hours, the calcination temperature is 520°C, and the calcination time is 3.2 hours; in step (2), 6.4 mmol of α-Fe2O3, 1.84 mmol of citric acid, 10.00 mL of glycerol and 20.00 mL of anhydrous ethanol are added, and the hydrothermal temperature is 160℃, hydrothermal time is 12 hours, calcination temperature is 500℃, calcination time is 5 hours; in step (3), add 3.0mL of concentrated ammonia water, 0.50mL of hydrazine hydrate, add 1.0g of 4α-Fe2O3 / BiFeO3, water bath temperature is 70℃, water bath time is 20 minutes; other parameters and steps are exactly the same as in Example 1, and rGO (1.0wt%)-4α-Fe2O3 / BiFeO3 gas sensitive material is obtained. Example 6
[0041] Compared with Example 1, the difference is that in step (1), 10 mmol of CH3COONa·4H2O is added, the water bath temperature is 55°C, the water bath time is 1.3 hours, the calcination temperature is 550°C, and the calcination time is 2.8 hours; in step (2), 6.4 mmol of α-Fe2O3, 1.792 mmol of citric acid, 10.00 mL of glycerol and 40.00 mL of anhydrous ethanol are added, and the hydrothermal temperature is 16 5℃, hydrothermal time is 11 hours, calcination temperature is 520℃, calcination time is 4.5 hours; in step (3), add 3.5mL of concentrated ammonia water, 0.50mL of hydrazine hydrate, add 0.67g of 4α-Fe2O3 / BiFeO3, water bath temperature is 80℃, water bath time is 40 minutes; other parameters and steps are exactly the same as those in Example 1, and rGO (1.5wt%)-4α-Fe2O3 / BiFeO3 gas sensitive material is obtained. Example 7
[0042] Compared with Example 1, the difference is that in step (1), 7.5 mmol of CH3COONa·4H2O is added, the water bath temperature is 70°C, the water bath time is 1.2 hours, the calcination temperature is 490°C, and the calcination time is 2.6 hours; in step (2), 12.8 mmol of α-Fe2O3, 1.808 mmol of citric acid, 10.00 mL of glycerol and 20.00 mL of anhydrous ethanol are added, the hydrothermal temperature is 170°C, the hydrothermal time is 14 hours, the calcination temperature is 480°C, and the calcination time is 4 hours; in step (3), 2.0 g of 8α-Fe2O3 / BiFeO3 is added; the other parameters and steps are exactly the same as in Example 1, and rGO (0.5wt%)-8α-Fe2O3 / BiFeO3 gas sensitive material is obtained. Example 8
[0043] Compared with Example 1, the difference is that in step (1), 8.5 mmol of CH3COONa·4H2O is added, the water bath temperature is 60°C, the water bath time is 1 hour, the calcination temperature is 500°C, and the calcination time is 3 hours; in step (2), 12.8 mmol of α-Fe2O3, 1.824 mmol of citric acid, 10.00 mL of glycerol and 40.00 mL of anhydrous ethanol are added, the hydrothermal temperature is 160°C, the hydrothermal time is 11 hours, the calcination temperature is 600°C, and the calcination time is 3 hours; in step (3), 3.0 mL of concentrated ammonia water, 0.50 mL of hydrazine hydrate, 1.0 g of 8α-Fe2O3 / BiFeO3 are added, the water bath temperature is 70°C, and the water bath time is 20 minutes; the other parameters and steps are exactly the same as in Example 1, and rGO (1.0 wt%)-8α-Fe2O3 / BiFeO3 gas sensitive material is obtained. Example 9
[0044] Compared with Example 1, the difference is that in step (1), 8.8 mmol of CH3COONa·4H2O is added, the water bath temperature is 50°C, the water bath time is 1.5 hours, the calcination temperature is 520°C, and the calcination time is 3.4 hours; in step (2), 12.8 mmol of α-Fe2O3, 1.792 mmol of citric acid, 10.00 mL of glycerol and 30.00 mL of anhydrous ethanol are added, and the hydrothermal temperature is 1 80℃, hydrothermal time is 12 hours, calcination temperature is 460℃, calcination time is 4.5 hours; in step (3), add 3.5mL of concentrated ammonia water, 0.50mL of hydrazine hydrate, add 0.67g of 8α-Fe2O3 / BiFeO3, water bath temperature is 80℃, water bath time is 40 minutes; the remaining parameters and steps are exactly the same as those in Example 1, and rGO (1.5wt%)-8α-Fe2O3 / BiFeO3 gas sensitive material is obtained. Example 10
[0045] The samples synthesized in Examples 1-9 were mixed and ground into a moderately viscous liquid in a molar ratio of 2 to 5:1 between the sample and anhydrous ethanol, and the liquids were evenly coated on the sensor components, and the gold electrodes of the sensor components were correspondingly welded to the base, and then the nickel-chromium resistance wire was assembled on the base, and aged at 80°C to 100°C for 2 to 5 days to obtain an isopropyl alcohol sensor. Comparative Example 1
[0046] 5.0 mmol of FeSO4·7H2O and 8.8 mmol of CH3COONa·4H2O were added to 50.00 mL of deionized water, stirred in a 70°C water bath for 1 hour, then centrifuged and dried to obtain yellow powder α-FeOOH, which was calcined at 500°C for 3 hours to obtain α-Fe2O3. Comparative Example 2
[0047] (1) Add 5.0 mmol of FeSO4·7H2O and 7.5 mmol of CH3COONa·4H2O to 50.00 mL of deionized water, stir and react in a 50°C water bath for 1.2 hours, then centrifuge and dry to obtain yellow powder α-FeOOH, which is calcined at 450°C for 2.5 hours to obtain α-Fe2O3.
[0048] (2) Add 1.6 mmol Bi(NO3)3·5H2O, 1.6 mmol Fe(NO3)3·9H2O, 1.76 mmol citric acid and 6.4 mmol α-Fe2O3 to a mixture of 10.00 mL glycerol and 20.00 mL anhydrous ethanol, and perform hydrothermal reaction at 150°C for 14 hours. After the reaction, cool to room temperature, wash and dry, and finally calcine at 400°C for 5 hours to obtain 4α-Fe2O3 / BiFeO3. Comparative Example 3
[0049] (1) Add 5.0 mmol of FeSO4·7H2O and 8.8 mmol of CH3COONa·4H2O to 50.00 mL of deionized water, stir and react in a 70°C water bath for 1 hour, then centrifuge and dry to obtain yellow powder α-FeOOH, which is calcined at 500°C for 3 hours to obtain α-Fe2O3.
[0050] (2) Add 1.6 mmol Bi(NO3)3·5H2O, 1.6 mmol Fe(NO3)3·9H2O, 1.8 mmol citric acid and 9.6 mmol α-Fe2O3 to a mixture of 10.00 mL glycerol and 30.00 mL anhydrous ethanol, and perform hydrothermal reaction at 160°C for 12 hours. After the reaction is completed, cool to room temperature, wash and dry, and finally calcine at 500°C for 4 hours to obtain 6α-Fe2O3 / BiFeO3. Comparative Example 4
[0051] (1) Add 5.0 mmol of FeSO4·7H2O and 10 mmol of CH3COONa·4H2O to 50.00 mL of deionized water, stir and react in a 60°C water bath for 1.5 hours, then centrifuge and dry to obtain yellow powder α-FeOOH, which is calcined at 550°C for 3.5 hours to obtain α-Fe2O3.
[0052] (2) Add 1.6 mmol Bi(NO3)3·5H2O, 1.6 mmol Fe(NO3)3·9H2O, 1.84 mmol citric acid and 12.8 mmol α-Fe2O3 to a mixture of 10.00 mL glycerol and 40.00 mL anhydrous ethanol, and perform hydrothermal reaction at 180°C for 10 hours. After the reaction, cool to room temperature, wash and dry, and finally calcine at 600°C for 3 hours to obtain 8α-Fe2O3 / BiFeO3. Comparative Example 5
[0053] The samples synthesized in Comparative Examples 1-4 and anhydrous ethanol were mixed in a molar ratio of 2 to 5:1 and ground into a moderately viscous liquid, and then evenly coated on the sensor devices, and the gold electrodes of the sensor devices were welded to the base respectively, and then the nickel-chromium resistance wire was assembled on the base, and aged at 80°C to 100°C for 2 to 5 days to obtain 4 isopropyl alcohol sensors.
[0054] Experimental Example 1
[0055] Figure 1 The morphology of the samples obtained in Example 2 and Comparative Examples 1 and 3. Figure 1 As shown, the gas-sensitive material prepared in Example 2 is composed of nanorod-shaped α-Fe2O3, nanoparticle-shaped BiFeO3 and thin film-shaped rGO, wherein the α-Fe2O3 is composed of nanorods with a diameter of 30 to 40 nm and a length of 400 to 600 nm, and the morphology of BiFeO3 is composed of nanoparticles with a diameter of 600 nm to 800 nm; the nanoparticle-shaped BiFeO3 is uniformly attached to the nanorod-shaped α-Fe2O3, and the thin film-shaped rGO is doped between the nanorod-shaped α-Fe2O3 to which the nanoparticle-shaped BiFeO3 is attached, and the size range of the rGO film is 50 to 600 nm; Figure 2 (a) is a SEM image of a sample synthesized in Comparative Example 1, in which α-Fe2O3 is composed of nanorods with a diameter of 30 to 40 nm and a length of 400 to 600 nm; Figure 2(b) is a SEM image of the synthetic sample of Comparative Example 3. The morphology of BiFeO3 in Comparative Example 3 is composed of nanoparticles with a diameter of 600nm to 800nm. The nanoparticle-like BiFeO3 is uniformly attached to the nanorod-like α-Fe2O3 to form a 6α-Fe2O3 / BiFeO3 composite material. Example 2 Compared with Comparative Examples 1 and 3, the rGO film not only increases the specific surface area of the material, providing more active sites for isopropanol gas analysis adsorption-desorption, but also has good intrinsic electron mobility, improves the conductivity of the semiconductor material, and improves the response of the gas sensitive material to isopropanol gas.
[0056] Experimental Example 2
[0057] Figure 3 (a) is the XRD spectrum of the samples synthesized in Comparative Examples 1-4. The XRD spectrum shows that BiFeO3 is consistent with the R3c rhombus structure (JCPDS: 86-1518), and the hexagonal α-Fe2O3 (JCPDS: 33-0664) is consistent with the position of the α-Fe2O3 peak obtained in Comparative Example 1. The corresponding diffraction peak position of α-Fe2O3 / BiFeO3 is consistent with the diffraction peak position of α-Fe2O3 (JCPDS: 33-0664) and BiFeO3 (JCPDS: 86-1518), indicating that the α-Fe2O3 / BiFeO3 binary composite material is successfully synthesized. Figure 3 (b) is the XRD spectrum of the synthesized sample of Example 1-3. The nanoparticle-shaped BiFeO3 is consistent with the R3c rhombic structure (JCPDS: 86-1518), and the position of the nanorod-shaped α-Fe2O3 peak is consistent with the hexagonal α-Fe2O3 (JCPDS: 33-0664). Due to the low rGO content (0.5-1.5wt%) in the gas sensitive material and the disordered stacking of rGO sheets, no diffraction peak appears. This shows that the gas sensitive material doped with rGO was successfully synthesized.
[0058] Experimental Example 3
[0059] The response capability of each gas sensor prepared in Example 10 and Comparative Example 5 was tested by using air and 25ppm isopropanol gas at 137°C. The results are shown in Table 1 below. By comparing the gas-sensitive responses of different ratios of α-Fe2O3 / BiFeO3 and α-Fe2O3, the 6α-Fe2O3 / BiFeO3 sensitive material has the highest response to isopropanol gas, indicating that α-Fe2O3:BiFeO3 is the best composite ratio when 6:1. When rGO of different mass ratios is introduced, it can be found from the table that the response to 25ppm isopropanol gas at 137°C is tested. Compared with the two-component α-Fe2O3 / BiFeO3 with different proportions, the response of the three-component is significantly higher than that of the two-component α-Fe2O3 / BiFeO3 and α-Fe2O3. The rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 sensitive material has the highest response to isopropanol gas, which is 1.27 and 4.42 times that of 6α-Fe2O3 / BiFeO3 and pure α-Fe2O3, respectively. This shows that the gas-sensing properties of α-Fe2O3 can be greatly improved by preparing rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 sensitive material.
[0060]
[0061] Experimental Example 4
[0062] like Figure 4 As shown, by testing the selectivity of each gas sensor prepared in Example 10 and Comparative Example 5, the response to various gases at 25ppm was tested at 137°C. By testing the response comparison of 25ppm ammonia, acetone, ethanol, ethylene glycol, n-butanol and n-hexanol, the results show that the response of rGO (1.0wt%) -6α-Fe2O3 / BiFeO3 gas sensitive material to isopropanol gas is much greater than that of other gases, indicating that the material has good selectivity, indicating that based on the unique surface characteristics and oxygen adsorption performance of BiFeO3, the selectivity and anti-interference ability of rGO (1.0wt%) -6α-Fe2O3 / BiFeO3 gas sensitive material to isopropanol gas are improved.
[0063] Experimental Example 5
[0064] Stability is crucial for the practical application of gas sensors. In order to verify the stability of the material, the gas sensor based on rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 was repeatedly tested 6 times at 137°C for 25ppm isopropanol gas within 32 days. Figure 5 As shown, the fluctuations of the 6 test results are small and the differences are basically the same, which shows that the gas sensor based on this material has good stability.
[0065] Experimental Example 6
[0066] Figure 6 The gas-sensitive responses of α-Fe2O3, 6α-Fe2O3 / BiFeO3 and rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 to 25ppm isopropanol gas at different temperatures are shown in the figure. It can be found from the figure that with the increase of temperature, the response first increases and then decreases, reaching the highest response at 137°C, indicating that 137°C is the optimal operating temperature. As shown in Table 2, compared with the prior art, the operating temperature of rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 gas-sensitive material is significantly lower, thereby reducing energy consumption in gas detection, making it more energy-saving and environmentally friendly. This is because the measured response is generated by the process of adsorption and reaction of oxygen in the adsorbed air with the injected target gas on the surface of the material. The increase in temperature response value is achieved by heating to overcome the activation energy of the two processes. The decrease in response value is due to the fact that when a certain temperature is reached, the adsorption and desorption of the gas reaches equilibrium. If the temperature is increased again, the movement of gas molecules adsorbed on the surface of the material will be accelerated to desorb, weakening the reaction of the gas surface. Compared with the existing α-Fe2O3 two-component composite material sensor, the operating temperature of the rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material synthesized in the present invention for isopropanol gas detection is greatly reduced.
[0067] Experimental Example 7
[0068] Figure 7 The following is a test chart of the response-recovery time of the rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material to 25ppm isopropanol gas at 137°C. It can be found from the figure that the response time is 16s and the recovery time is 29s. As shown in Table 2, compared with the existing technology, the response and recovery time of the rGO (1.0wt%)-6α-Fe2O3 / BiFeO3 gas sensitive material is shorter, indicating that it has a stronger response-recovery ability, which provides certain possibilities for the real-time detection application of sensors.
[0069]
Claims
1. An isopropyl alcohol gas sensitive material, Features: Including nanorod-shaped α-Fe 2 O 3 , BiFeO nanoparticles 3 and thin film rGO, the nanoparticle BiFeO 3 Uniformly attached to the nanorod-shaped α-Fe 2 O 3 The thin film rGO is doped with BiFeO nanoparticles. 3 Nanorod-like α-Fe 2 O 3 The content of the thin film rGO is 0.50-1.50wt% of the isopropanol gas sensitive material, and the nanorod-shaped α-Fe 2 O 3 With nanoparticle BiFeO 3 The molar ratio is 4 to 8:
1.
2. The isopropyl alcohol gas sensitive material according to claim 1, It is characterized in that The content of the thin film rGO is 1.0wt% of the isopropanol gas sensitive material, and the nanorod-shaped α-Fe 2 O 3 With nanoparticle BiFeO 3 The molar ratio is 6:
1.
3. A method for preparing the isopropyl alcohol gas sensitive material as claimed in claim 1, It is characterized in that The steps include: S1. FeSO 4 7H 2 O、CH 3 COONa·4H 2 O was added to deionized water, and after being completely dissolved, a water bath reaction was performed, followed by centrifugation and drying to obtain a yellow powder precursor α-FeOOH, which was then calcined to obtain nanorod-shaped α-Fe 2 O 3 ; S2. Change Bi(NO 3 ) 3 ·5H 2 O, Fe(NO 3 ) 3 9H 2 O, citric acid and nanorod-shaped α-Fe 2 O 3 Dissolve in a mixture of glycerol and anhydrous ethanol, perform a hydrothermal reaction, and then wash, dry, and calcine to obtain α-Fe 2 O 3 / BiFeO 3 ; S3. Add graphene oxide to deionized water and disperse it evenly, then add concentrated ammonia, hydrazine hydrate and α-Fe 2 O 3 / BiFeO 3 ; Stir in a water bath to generate a precipitate, then centrifuge and dry the precipitate to obtain rGO-α-Fe 2 O 3 / BiFeO 3 The gas sensitive material is isopropyl alcohol gas sensitive material.
4. The method for preparing the isopropyl alcohol gas sensitive material according to claim 3, It is characterized in that In step S1, FeSO 4 7H 2 O and CH 3 COONa·4H 2 The molar ratio of O is 1:1.5-2, the water bath reaction temperature is 50-70°C, and the reaction time is 1.0-1.5 hours; the calcination temperature is 450-550°C, and the calcination time is 2.5-3.5 hours.
5. The method for preparing the isopropyl alcohol gas sensitive material according to claim 3, It is characterized in that In step S2, Bi(NO 3 ) 3 ·5H 2 O, Fe(NO 3 ) 3 9H 2 O, citric acid and α-Fe 2 O 3 The molar ratio of glycerol to anhydrous ethanol is 1:1:1.1-1.15:4-8, the volume ratio of glycerol to anhydrous ethanol is 1:2-4, the hydrothermal temperature is 150-180°C, the reaction time is 10-14 hours; the calcination temperature is 400-600°C, and the calcination time is 3-5 hours.
6. The method for preparing the isopropyl alcohol gas sensitive material according to claim 3, It is characterized in that In the step S3, the volume ratio of hydrazine hydrate to concentrated aqueous ammonia is 1:5-7, the water bath temperature is 70-90° C., and the water bath reaction time is 20-40 minutes.
7. An application of the isopropyl alcohol gas sensitive material as claimed in claim 1, It is characterized in that The isopropyl alcohol gas sensitive material is applied to an isopropyl alcohol sensor.
Citation Information
Patent Citations
FexOy-based inorganic nanocomposite and preparation method thereof
CN102764654A
Novel quick-response bismuth ferrite gas sensitive material as well as preparation method and application thereof
CN105203598A
